Development of a high-throughput device for liquid-phase microextraction coupled with gas chromatography-mass spectrometry for the determination of benzene derivatives in environmental water. Issue 25 (7th June 2021) - Li, Zhiqiang; Guo, Zhian; Chen, Xiaomei; Liu, Jie; Xu, Yidong; Wang, Yi; Zhao, Jingchan
Abstract : A liquid phase microextraction device that does not require centrifugation and transfer of solvent. Abstract : A device coupled with an automatic gas chromatography injection sampler for high-throughput liquid–liquid microextraction has been proposed in this study. This study's main objective was to devise a trap vial directly placed in an automatic liquid sampler (ALS) to collect and inject the extractant without a transfer step. Sixteen groups of microextraction procedures were performed simultaneously to increase the overall efficiency. The experimental parameters of the extraction method were optimized using a central composite design. Under the optimal conditions, the benzene derivatives' calibration curve was linear in the range of 0.1–200 μg L −1 . The limit of detection (LOD) ranged from 0.016 to 0.16 μg L −1, and the limit of quantitation (LOQ) ranged from 0.046 to 0.50 μg L −1 . The enrichment factors (EFs) ranged from 254 to 1094. Intraday and interday precision were found to be in the range of 2.2–6.2% ( n = 3) and 4.0–6.3% ( n = 9), respectively. The relative recovery of the four aqueous samples ranged from 69% to 121%. These experimental results indicated that the proposed device is reliable. Furthermore, it is simple, convenient and high-throughput.